Does an Unplanned Pregnancy have Long-Term Implications for Mother-Child Relationships? - Nelson, Jackie A. (J Fam Issues, 2011)
The effect of pregnancy planning on the quality of mother-adolescent relationships 15 years later was examined among 373 first-time parents and 472 experienced parents using a mediated moderation model. Among first-time mothers only, the experience of an unplanned pregnancy was related to higher maternal depressive symptoms when mothers also experienced high parenting stress over the first three years. High maternal depressive symptoms over those early years were, in turn, related to more conflict and hostility in the parent-adolescent relationship according to mother and adolescent reports. Additionally, interactions between parity and pregnancy planning revealed that experienced mothers with unplanned pregnancies had the most early parenting stress, though an unplanned pregnancy and high parenting stress did not predict higher depressive symptoms for these mothers as it did for first-time mothers. The findings provide support for the importance of early parenting emotions and experiences on later parent-adolescent relationship quality.